The Neurologist's Role in Patients with Mild Cognitive Impairment and Mild Alzheimer's Disease Dementia. (20th December 2022) - Pruzin, Jeremy J.; Brunton, Stephen; Alford, Susan; Hamersky, Carol; Sabharwal, Anup; Gopalakrishna, Ganesh
Abstract: Background: Alzheimer's disease (AD) is a progressive neurodegenerative disease and the most common cause of dementia. Mild cognitive impairment (MCI) affects >10% of US adults over the age of 70 and represents a transitional stage between healthy aging and dementia. Multiple factors influence the path to care through the health system. This study sought to better understand the medical journey of patients with all‐cause MCI and mild AD dementia (ADD) to identify opportunities for improvement. Method: An anonymous online survey was conducted in a cross‐sectional US‐population of 103 patients with self‐reported diagnosis of MCI/mild ADD, 150 care partners of patients with MCI/mild ADD, and 75 neurologists. Result: In the most common medical journey for patients (73% of patients), half of patients/care partners (51%) reported they received their diagnosis from a neurologist. The most common reasons patients/care partners initiated discussions with a healthcare provider were symptoms interfering with activities of daily life (51%), symptoms not resolving (46%), encouragement from family or friends (44%), and symptoms worsening in degree of discomfort/frequency (43%). Most patients/care partners (23%) reported receiving a misdiagnosis prior to receiving a formal diagnosis of MCI/mild ADD. Half of neurologists (52%) view themselves as the coordinator of care for patients with MCI/mild ADD; whereas 35% of patients/care partners view them as such. At the time of diagnosis, most neurologists (83%) reported discussing with patients the potential causes of MCI/mild ADD. Most neurologists (84%) reported following American Academy of Neurology guidelines (AAN) for treatment and management of patients with MCI/mild ADD. For ongoing care, treatments most commonly prescribed/recommended by neurologists included mental exercises (84%), general improvements in lifestyle (84%), acetylcholinesterase (AChE) inhibitors (78%), social interaction (75%), and NMDA antagonists (73%). Conclusion: Neurologists are often the healthcare provider diagnosing MCI/mild ADD however patients frequently experience misdiagnosis in their medical journey. Neurologists are not viewed as coordinators of care by most patients. Positioning neurologists as coordinators of MCI/mild ADD care and equipping them with the right resources may help patients obtain a diagnosis and treatment sooner.